PERFORMANCE OF THE REGIONAL SECRETARIAT GENERAL BUREAU OF CENTRAL SULAWESI PROVINCE - Abas, Cakrawali; Waris, Irwan; Nawawi, Muh; Hasbullah, Hasbullah; Susanti, Ani (Penerbit Lafadz Jaya, 2024)
This study aims to determine how the performance of the General Bureau of the Regional Secretariat of Central Sulawesi Province. In this study researchers used the theory of Moeheriono (2012: 162-163) which consists of criteria of Responsiveness (responsiveness), Responsibility (responsibility) and Accountability (accountability). The research method used is a qualitative descriptive research type. Data collection was carried out using observation, documentation, and interview methods. The determination and number of informants in this study are parties who are considered to know in depth various matters concerning research problems totaling 5 (five) people. While data analysis techniques include data collection, data condensation, data presentation, and conclusion drawing/verification. The results of this study show that the performance of the General Bureau of the Regional Secretariat of Central Sulawesi Province has not run optimally, this is due to the non-achievement of performance indicators used in this study such as aspects of responsiveness that have not been maximized due to Human Resources within the scope of the General Bureau of the Regional Secretariat of Central Sulawesi Province which is still limited, especially in the placement of executive positions not in accordance with the competence of employees in the agency in carrying out its duties. The aspect of responsibility has not run optimally due to frequent delays in completing tasks due to frequent procrastination of work, the accountability aspect has been running well in the application of the Core Values of ASN BerAKHLAK but still needs to be socialized again, considering that these values are new things that need to be applied and used as guidelines for the implementation of duties by each ASN in providing services.